2015
DOI: 10.1044/2015_aja-14-0074
|View full text |Cite
|
Sign up to set email alerts
|

Speech, Spatial and Qualities of Hearing Scale (SSQ) and Spatial Hearing Questionnaire (SHQ) Changes Over Time in Adults With Simultaneous Cochlear Implants

Abstract: Purpose The purpose of the present study is to evaluate the changes over time of the Spatial Hearing Questionnaire (SHQ; Tyler, Perreau, & Ji, 2009) and the Speech, Spatial and Qualities of Hearing Scale (SSQ; Gatehouse & Noble, 2004) in adults with simultaneous bilateral cochlear implants by collecting data for 2 years after implantation. Method Nineteen postlingual subjects participated in this study. Average age at implant was 63 years. The s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
24
2
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(32 citation statements)
references
References 28 publications
(30 reference statements)
3
24
2
3
Order By: Relevance
“…This increase in performance presumably occurs as they adapt to perceiving sound through the implant, which is very different than the acoustic hearing they had previously. However, such improvement in adults appears to plateau after only about 1 year ( Ruffin, Tyler, Witt, Dunn, Gantz, & Rubinstein, 2007 ; Zhang et al., 2015 ). A longitudinal investigation of speech identification performance of both adults and children with CIs demonstrated that adults’ speech recognition scores peaked prior to 2 years postimplantation, while pediatric CI users’ scores continued to improve throughout the 4 years of the study ( Oh et al., 2003 ).…”
Section: Discussionmentioning
confidence: 99%
“…This increase in performance presumably occurs as they adapt to perceiving sound through the implant, which is very different than the acoustic hearing they had previously. However, such improvement in adults appears to plateau after only about 1 year ( Ruffin, Tyler, Witt, Dunn, Gantz, & Rubinstein, 2007 ; Zhang et al., 2015 ). A longitudinal investigation of speech identification performance of both adults and children with CIs demonstrated that adults’ speech recognition scores peaked prior to 2 years postimplantation, while pediatric CI users’ scores continued to improve throughout the 4 years of the study ( Oh et al., 2003 ).…”
Section: Discussionmentioning
confidence: 99%
“…This may have been too short to have gained enough individual experience with bimodal listening in all situations that are assessed by the SSQ-B ( 57 ). Other longitudinal studies with CI-patients evidence however, that most improvement seen in the SSQ takes place during the first 6 months and that a stable plateau is reached within this interval ( 7 ). Also, improvements in sentence comprehension in quiet and noise essentially reach a stable plateau within 6 months of CI use, while improvements in the FBE test continue until 12 months post-implantation ( 58 ).…”
Section: Discussionmentioning
confidence: 99%
“…With technological progress, relaxation of criteria for cochlear implantation and the aim to achieve binaural hearing, bimodal provision, i.e., a cochlear implant (CI) in one ear and a hearing aid (HA) at the other ear, is used by a growing number of CI-patients. Overall, this combination of electrical and acoustical hearing has benefits, but this is not necessarily true for each user and all types of conditions ( 1 – 7 ). Given the relatively limited body of literature on bimodal hearing and because of progress in CI- and HA-technology, further research on the benefits of bimodal hearing is warranted.…”
Section: Introductionmentioning
confidence: 99%
“…Participants were also asked to rate on a scale how hard they need to concentrate when listening. The questions were based on Speech, Spatial and Qualities of Hearing Scale (SSQ) and Spatial Hearing Questionnaire (SHQ) (Zhang et al, 2015).…”
Section: Self-reported Hearing Difficultiesmentioning
confidence: 99%